"Taking Responsibility": Conflict Transformation and the Loyalist Paramilitaries of Northern Ireland - Sloan, Brittany Ilyssa (Tufts Archival Research Center, 2005)
Since the Troubles, Northern Ireland's Protestant loyalist paramilitary organizations, the Ulster Defense Association and the Ulster Volunteer Force, have started on a road of fundamental change in pursuit of sustainable peace. Intrinsic to this process has been the theory of conflict transformation, which has become loyalist gospel; however, a means of assessing the extent to which the loyalist paramilitaries are adhering to this creed remains limited. Built on the seminal work of scholar John Paul Lederach and on the loyalists' own doctrine of "sharing responsibility," this research establishes a framework to assess the extent to which the loyalist paramilitaries are engaging in conflict transformation. This study presents a comprehensive analysis of the loyalist initiatives within the tripartite framework of restructuring relationships, building capacity, and reconceptualizing norms for conflict transformation and analyzes each in accordance with three indicators of taking responsibility â behaving correctly, being accountable, and acting independently. This process elucidates not only what the loyalists are doing to in support of conflict transformation, but also the degree of their success.